Network competition - the co-existence of hub-and-spoke and point-to-point - Marco Alderighi; Alessandro Cento; Peter Nijkamp; Piet Rietveld (European Regional Science Association (ERSA), 2005)
Airlines network choices are analysed to describe the co-existence of alternative business models: the full service model based on the hub-and-spoke (HS) system and the low cost model based on point-to-point (PP) system. The analysis is carried on both theoretically and empirically. In the theoretical part, we show that the rise of the low costs business model can be the consequence of a simple two-player game. When two carriers compete in designing their network configurations (HS or PP), asymmetric equilibria emerge, i.e. one carrier will choose HS and the other PP. Full service carriers are stuck to a HS configuration to serve intercontinental destinations, whilst non-flag carriers implement a point-to-point network. In the second part, the recent network evolution in Europe is empirically evaluated by means of different spatial measures of concentration, such as Gini index, Freeman centrality index and Bonacich centrality. In addition, we also provide an airline-specific measure of centrality based on scheduled time comparison of direct to one-stop services. Spatial measures of centrality capture a reduction of centrality in non-flag carriers and small changes in the network centrality of flag carriers. Indeed, the time-based measure of centrality suggests an increase of centrality of flag carriers.
Keywords: 330